Tourist Information Centres in The Time of A Pandemic - Karina TESSAR (Communications of International Proceedings, 2021)
The COVID-19 coronavirus pandemic had a significant impact on many branches of the economy. Its negative effects badly affected the tourist industry. The closure of international airspace or land borders, limits on the number of places in hotels and other accommodation establishments, or the total freeze of their activities, as in the case of gastronomy, culture, recreational facilities or other tourist attractions, resulted in the reduced tourist traffic and significant economic losses. However, tourist traffic has not come to entire halt – still done are for example business, so some experts talk about an opportunity for the development of domestic and local tourism (Szansa… 2020). As mental fatigue (Heitzman 2020) caused by stress and the introduction of many restrictions grows, some people return to their habits and travel. A year has passed since the announcement of the pandemic in Poland and also many business entities are coming back to their operations or trying to continuously operate in these new circumstances. These include Tourist Information Centres. The example of two model tourist information centres in Szczecin shows how the pandemic influenced, among others, the functioning of offices, the number of visitors, the method of communication, and the ratio of information provided in analogue and digital form. Research data was compared to the year before the pandemic. Foresight research, literature review and expert interviews were used in this study. This research has shown that despite the transfer of a large part of services to the Internet, humans are still the most reliable source of information.
Keywords: Tourist Information; Pandemic; Globalization